2018
DOI: 10.1002/lary.27740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of transoral robotic surgery: Nationwide results from the first 5 years of adoption

Abstract: Objectives To compare long‐term oncologic outcomes and adjuvant therapies for patients treated with transoral robotic surgery (TORS), nonrobotic surgery, or transoral laser microsurgery (TLM). Study Design A retrospective analysis of the National Cancer Database (2010–2014). Methods Patients with clinical tumor (T)1 and T2 oropharyngeal squamous cell carcinomas (OPSCC) were classified into those receiving TORS versus nonrobotic surgery versus TLM. Univariate and multivariate survival analyses were conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 33 publications
4
40
0
5
Order By: Relevance
“…3 Li et al reported a PMR of 16.5% in T1/T2 patients, which was lower than both nonrobotic surgery and transoral laser microsurgery (28.4% and 21.4%, respectively). 15 Zevallos et al demonstrated a PMR of 16.8% for TORS patients of all T classifications as compared to 28.3% for other transoral, nonrobotic approaches, although this difference was not significant in their multivariable model. 21 A study of low-classification (T1/T2) OPSCC in the NCDB by Cracchiolo et al yielded an overall PMR of 24% for all primary surgical patients.…”
Section: Discussionmentioning
confidence: 86%
“…3 Li et al reported a PMR of 16.5% in T1/T2 patients, which was lower than both nonrobotic surgery and transoral laser microsurgery (28.4% and 21.4%, respectively). 15 Zevallos et al demonstrated a PMR of 16.8% for TORS patients of all T classifications as compared to 28.3% for other transoral, nonrobotic approaches, although this difference was not significant in their multivariable model. 21 A study of low-classification (T1/T2) OPSCC in the NCDB by Cracchiolo et al yielded an overall PMR of 24% for all primary surgical patients.…”
Section: Discussionmentioning
confidence: 86%
“…TORS has been shown to be safe and at least as effective as traditional approaches and has reduced morbidity and quality of life in head and neck surgery . TORS has shown preservation of laryngopharyngeal function without compromising oncologic outcomes and has reduced the need for adjuvant therapy using an “inside‐out” approach . In a more recent study, TORS has also been shown to have a lower rate of positive margins when compared to non‐robotic surgery, particularly in high‐volume centers …”
Section: Resultsmentioning
confidence: 99%
“…Both variables were used to isolate surgical modalities. As in previous studies, laser surgery was identified via NCDB surgery of the primary site codes 14 (local destruction with laser) and 25 (local laser excision) and open surgery via the surgical approach variable . To eliminate overlap for laser patients, only those with laparoscopic listed under surgical approach were included.…”
Section: Methodsmentioning
confidence: 99%